Paleomagnetic Constraint of the Brunhes Age Sedimentary Record From Lake Junín, Peru - Hatfield, Robert G.; Stoner, Joseph S.; Solada, Katharine E.; Morey, Ann E.; Woods, Arielle; Chen, Christine Y.; McGee, David; Abbott, Mark B.; Rodbell, Donald T. (Frontiers in Earth Science, 2020)
Normalized remanence, a proxy for relative geomagnetic paleointensity, along with radiocarbon and U-Th dates, facilitates the generation of a well-constrained chronology for sediments recovered during International Continental Scientific Drilling Program (ICDP) coring of Lake Junín, Peru. The paleomagnetic record of the ~88 meter stratigraphic section from Lake Junín was studied, and rock magnetic variability constrained, through analysis of 109 u-channel samples and 56 discrete samples. Downcore variations in sediment lithology reflect climate and hydrological processes over glacial-interglacial time frames and these changes are strongly reflected in the bulk magnetic properties. Glacial sediments are characterized by higher detrital silt content, higher magnetic susceptibility and magnetic remanence values, and a magnetic coercivity that is characteristic of ferrimagnetic (titano)magnetite and/or maghemite. Interglacial sediments and low lake-level facies are dominated by carbonate lithologies and/or peat horizons that result in lower magnetic concentration values. Sediments with moderately high NRM intensity (>1 x 10-3 A/m) have well-resolved component directions and inclination values that vary around geocentric axial dipole expectations. This remanence value can be used as a threshold to filter the lowest quality paleomagnetic data from the record. Normalized NRM intensity values are also sensitive to lithologic variability, but following NRM remanence filtering, only the highest quality ferrimagnetic dominated data are retained which then show no coherence with bulk magnetic properties. Constrained by the existing radiocarbon based chronology over the last 50 kyrs and 18 U-Th ages that are restricted to five interglacial sediment packages, filtered normalized remanence parameters compare well with global relative paleointensity stacks, suggesting relative variations in geomagnetic intensity are preserved. By adjusting the existing age-depth model we improve the correlation between the Junín normalized intensity record and a well-dated RPI stack and RPI model. We then incorporate these paleomagnetic tie points with the existing radiometric dates using a modeling approach to assess uncertainty and refine the age-depth model for Lake Junín. In combining relative and radiometric dating, the new age-depth model captures glacial-interglacial variations in sedimentation rate and improves the orbital-scale age model for the sediments accumulated in Lake Junín basin over most of the Brunhes.